Enhancement of Electrical and Thermomechanical Properties of Silver Nanowire Composites by the Introduction of Nonconductive Nanoparticles: Experiment and Simulation - Nam, Seungwoong; Cho, Hyun W.; Lim, Soonho; Kim, Daeheum; Kim, Heesuk; Sung, Bong J. (AMER CHEMICAL SOC, 2013)
Electrically conductive polymer nanocomposites have been applied extensively in many fields to develop the next generation of devices. Large amounts of conductive nanofillers in polymer matrices are, however, often required for a sufficiently high electrical conductivity, which in turn deteriorates the desired thermomechanical properties. We illustrate a novel but facile strategy to improve the electrical conductivity and the thermomechanical property of silver nanowire/polymer nanocomposites. We find that one may increase the electrical conductivity of silver nanowire/polymer nanocomposites by up to about 8 orders of magnitude by introducing silica nanoparticles with nanocomposites. The electrical percolation threshold volume fraction of silver nanowires decreases from 0.12 to 0.02. Thermomechanical properties also improve as silica nanoparticles are introduced. We carry out extensive Monte Carlo simulations to elucidate the effects of silica nanoparticles at a molecular level and find that van der Waals attractive interaction between silica nanoparticles and silver nanowires dominates over the depletion-induced interaction between silver nanowires, thus improving the dispersion of silver nanowires. Without silica nanoparticles, silver nanowires tend to aggregate, which is why additional silver nanowires are required for a desired electrical conductivity. On the other hand, with silica nanoparticles mixed, the electrical percolating network is likely to form at a smaller volume fraction of silver nanowires.
Keywords: ISOTROPIC CONDUCTIVE ADHESIVES; PERCOLATION-THRESHOLD; TRANSPARENT; NETWORKS; BEHAVIOR; FILMS